Preliminary AMISR-14 radar observations of F-region incoherent backscatter echoes at the Jicamarca Radio Observatory (JRO) - Apaza, Joab (2022)
Poster presented at the 2022 CEDAR Workshop, Austin-TX, USA, June 19-24